Pengaruh Sustainability Reporting terhadap Nilai Perusahaan Pertambangan di Indonesia: Systematic Literature Review dengan Pendekatan PRISMA 2020 - Syifa Aristawati; Erlyna Tri Rohmiatun (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2026)
Mining companies are increasingly required to demonstrate environmental, social, and governance (ESG) accountability through sustainability reporting (SR). However, empirical evidence regarding the impact of SR on firm value in Indonesia’s mining sector remains inconsistent. This study aims to systematically examine the relationship between sustainability reporting and firm value using legitimacy theory as the conceptual framework. A Systematic Literature Review was conducted following the PRISMA 2020 protocol, employing narrative and thematic synthesis. Peer-reviewed articles published between 2018 and 2025 were retrieved from Google Scholar, Garuda Portal, and SINTA databases using relevant keywords. From 4,260 initial records, 11 studies met the inclusion criteria after screening, deduplication, and quality appraisal using an adapted CASP checklist. The findings reveal three dominant patterns: most studies report a positive effect of SR on firm value through improved transparency, corporate reputation, and investor confidence; several studies find no significant relationship due to short-term investor orientation; while a minority report negative effects associated with low disclosure quality and greenwashing concerns. Furthermore, the effectiveness of SR is influenced by disclosure quality, corporate governance, profitability, and leverage. This study implies that sustainability reporting can enhance firm value when disclosures are credible, consistent, and material, supporting legitimacy theory and encouraging alignment with the GRI 14: Mining Sector 2024 standard.